The Greatest College Football Rivalries of All Time: The Civil War, the Iron Bowl, and Other Memorable Matchups - Gitlin, Martin (Rowman & Littlefield Publishers, 2014)
College football is one of the most popular sports in the United States. Fans follow their favorite team with unfailing loyalty, and nowhere do the colors come out more fervently than when rivals face off. These games bring out the passion, the rituals, and even the rage of football fans across the country. Whether based on history and tradition, or proximity and local pride, college rivalry games have an intensity unmatched by any other sporting event. The Greatest College Football Rivalries of All Time: The Civil War, the Iron Bowl, and Other Memorable Matchups showcases the best of these competitions. Martin Gitlin details game highlights, the history behind the rivalries, and how the fans, players, and coaches have impacted the matchups. The fourteen top rivalries are covered, including the always-intense battles between the Ohio State Buckeyes and the Michigan Wolverines, the great in-state rivalry between the Auburn Tigers and the Alabama Crimson Tide, and the historic contests between the Army Black Knights and the Navy Midshipmen. In addition to capturing the action of the games, this book also covers the personal stories that heighten the passion and intensity of the rivalries—including pranks pulled over the years by opposing fans. With stats and series highlights detailed in each entry, and featuring historical and contemporary photographs throughout its pages, The Greatest College Football Rivalries of All Time is a must-read for every fan of college football.